The Martian Chronicles: The Triple System - Herrera Ávila, Tatiana (2026)
This article discusses the story collection The Martian Chronicles by American author Ray Bradbury and analyzes the literary genres that are combined in it: science fiction, utopia and chronic. It will demonstrate how the text weaves from these genres, a clear, open and sometimes acidic critique of society, a warning rather than force on the scope of space exploration and the frightening possibility of repeating the cruel experience of the Conquest of America From an ethical perspective and humanist.